The rat cumulative allostatic load measure (rCALM): a new translational assessment of the burden of stress. Issue 1 (4th May 2019) - McCreary, J Keiko; Erickson, Zachary T; Paxman, Eric; Kiss, Douglas; Montina, Tony; Olson, David M; Metz, Gerlinde A S
Abstract: Determinants of lifetime health are complex and emphasize the need for robust predictors of disease risk. Allostatic load (AL) has become a clinical framework to estimate the cumulative biological burden associated with chronic stress. To assist knowledge translation in the developmental origins of health and disease field, clinically valid methods for reliable AL assessment in experimental models are urgently needed. Here, we introduce the rat cumulative allostatic load measure (rCALM), as a new preclinical knowledge translation tool to assess the burden of chronic stress. First, we identified an array of stress-associated physiological markers that are particularly sensitive to hypothalamic–pituitary–adrenal axis dysregulation by ancestral prenatal stress. Second, we determined which of these markers are susceptible to an intervention by environmental enrichment (EE) to mitigate AL. The markers most responsive to stress and EE therapy were assembled to become operationalized in the rCALM. Third, the new rCALM was validated for the ability to indicate future disease risks. The results show that the rCALM estimates the burden of chronic stress and serves as a proxy to estimate stress resilience and vulnerability to disease. Using the rCALM we showed that enrichment therapy can offset the adverse health outcomes linked to a high AL. Thus, the rCALM provides a model for the development of new test strategies that facilitate knowledge translation in preclinical animal models.